ISLAM DAN MADZHAB: ANALISIS DISTRIBUSI PENGIKUT MADZHABMADZHAB MU’THABARAH DI BERBAGAI BELAHAN DUNIA - Udin Supriadi; Mohammad Rindu Fajar Islamy; Wawan Hermawan (istinbath, 2020)
This article tries to present a map of the geographic distribution of the followers of Islamic fiqh schools, especially Madzãhibu al-Arba’ah al-Mu’tabarah, namely the Hanafî school, Mãlikî school, Syafi’i school, and Hanbalî school throughout the world. The spread of Islamic fiqh schools of al-mu’tabarah has reached various parts of the world from the birth of the first generation until today. Fiqh is one of the essential aspects that Islam is very concerned about. The legal aspects produced by the jurists who are istinbathed from the texts both al-Qur’an and hadith have colored the lives of Muslims in religious life. Hanafî, Mãlikî, Syafi’i, Hanbalî and others schools are manifestations of the Islamic scholars’ concern for the practice and rules of worship so that they become a bridge in the framework of taqarrub to Allah SWT through role models exemplified by Rosulullah SAW. This research study uses a Literature Review approach using interactive data analysis techniques. The results showed that the fiqh schools at least had their own unique regional bases that were not owned by the others.